(untitled) (Texas Journal of Philology, Culture and History, 2024)
The article examines the main and auxiliary themes of Isajon Sultan’s story “Wooden shoes” ("Yog`och Kovush"), the main idea of the work. The importance of the work in modern storytelling is noted